Effectiveness of the Buzzy Device in Managing Needle Pain in Children: A Systematic Review. - Tanghe, Loes; Borloo, Saar; Dewolf, Philippe; Toelen, Jaan; Waelkens, Isabelle; Gielissen, Nicole (Belgian Journal of Paediatrics, 2025)
Background: Needle procedures often cause pain and anxiety in children, highlighting the necessity for effective pain management strategies. This systematic review aimed to evaluate the effectiveness of the Buzzy® device, a non-pharmacological intervention combining cold and vibration, in managing paediatric needle pain using a standardized pain assessment tool. Methods: A systematic search was conducted in December 2024 using PubMed, CINAHL, Embase, and Google Scholar databases to identify randomized controlled trials. Inclusion criteria were studies involving children aged 2–18 years undergoing needle-related procedures, employing the Faces Pain Scale-Revised (FPS-R), and comparing the Buzzy® device against control groups or alternative interventions such as topical anesthetics, distraction techniques, or other non-pharmacological methods. Study quality was assessed using the Risk of Bias 2 (RoB 2) tool. Results: 8 RCTs comprising 1.569 pediatric participants were included. Studies consistently demonstrated significant pain reduction with Buzzy® compared to no intervention. Comparisons with topical anesthetics showed mixed results: Buzzy® provided rapid analgesia advantageous in emergency settings but was commonly less effective in pain reduction than topical anesthetics like EMLA cream. Buzzy® persistently outperformed other non-pharmacological methods, such as ShotBlocker® and DistrACTION® Cards, and was most effective when combined with distraction techniques. Risk of bias was moderate across studies, primarily due to the inability to blind participants and practitioners. Conclusion: Our work provides nuanced support for the claim that the Buzzy® effectively reduces needle-related procedural pain in children, particularly in acute clinical settings where a rapid onset of analgesia is required. Further research employing standardised methodologies is recommended to strengthen the evidence base for multimodal paediatric pain management strategies.